Toxic compounds of Curcuma aeruginosa causes necrosis of mice hepatocytes - Eka Pramyrtha Hestianah; Idha Kusumawati; Lucia Tri Suwanti; Sri Subekti (Faculty of Medicine, Universitas Trisakti, 2014)
BACKGROUNDPeople have been using Curcuma aeruginosa rhizome as a traditional herbal medicine as appetite stimulant, without realizing its side effects. Herbal plants contain tens to hundreds of compounds, some of which are toxic. The aim of this research was to determine which toxic compound of Curcuma aeruginosa rhizome has an impact on apoptosis and PARP-1 expression of hepatocytes in male mice.METHODSEighty eight male Balb C mice were divided into 10 groups treated respectively with Curcuma aeruginosa rhizome cloroform extract, methanol extract, essential oil, infusion, and press juice, at dosages of 0.004g/kgBW and 0.06g/kgBW, and 1 control group. The treatment was given orally once a day for 10 days and on the 11th day, the research animals were sacrificed, and their liver taken for histopathologic slide preparation with Apopteq Detection Kit, and immunofluorescence. Compounds in Curcuma aeruginosa rhizome were analyzed with gas chromatography/mass spectrometry. The data obtained were analyzed by one-way ANOVA, and Partial Least Squares to determine which compounds had an impact on murine hepatocytes.RESULTSThe result of one way ANOVA showed that the chloroform groups at dosages of 0.004g/kgBW and 0.06g/kgBW showed the highest apoptosis of mice’s hepatocytes (p<0.05). There were significant differences in PARP-1 expression between control and treatment groups. The highest PARP-1 expression was in the essential oil group at a dosage of 0.06g/kg BW (p<0.05).CONCLUSIONCurcuma aeruginosa rhizome given to mice orally causes necrosis of mice’s hepatocytes.